Existence of solution to first-order multipoint boundary value problems / Diana Sirmayunie Mohd Nasir - Mohd Nasir, Diana Sirmayunie (Research Management Institute (RMI), 2010)
In this manuscript we study initial value problems and boundary value problems for a first order ordinary differential equations. We establish the existence of solutions by the Banach Contraction Mapping Principals. Next we present the numerical methods for the above initial value problems, where the numerical comparison between the Euler and Runge-Kutta methods are being investigated. We prove the existence of solutions to the multipoint by Schaeffer fixed point theorem and uniqueness of solutions by the Contraction Mapping Principal.